Dakwah Qaryah Thayyibah’s (DQT) of Darul Ihsan Islamic Boarding School Muhammadiyah Sragen (DIMSA) as a Model of The Moderate Islam - Rohmat Suprapto; Mufanaetty Mufanaetty (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
This study aimed to examine (1) how the application of the Dawah Qaryah Thayyibah (DQT) method was, (2) whether the DQT method was effectivefor spreading moderate Islam, and (3) the obstacles in applying the method.This study used the qualitative method with the religious study approach, conducted at the Pondok Pesantren Darul Ihsan Muhammadiyah Sragenor DIMSA (the Darul Ihsan Muhammadiyah Islamic Boarding School of Sragen ~Eng.), Indonesia. The data were obtained based on open-ended question-based interviews with the key respondents. The data were then analyzed in three steps: reduction, presentation, and conclusion. The results showed the following: First, the DQT was carried out by sending the students to a community within a certain period to interact with the community, assisting both in religious and social activities in the community; therefore, there was an interaction between students and the wider community. Second, the DQT was effective for spreading moderateIslam, and the effectiveness was in two things: first, the students had a new awareness that there was diversity in society both in terms of religion, culture, and society, and thus the DQT method could reduce and minimize conflicts both in religious and social teachings and the weakness of humanity; second, there were some moderate values that could be developed using the DQT method, including tawazun (balance), ta’adul (justice), tasamuh (tolerance), and shura (deliberatio n ) to create an inclusive-participatory attitude. Third, the obstacle i n implementing the DQT method was the relatively short interaction time between studentsand the community; hence the results of internalizing moderate Islamic values had not been fully visible in real terms.